2020
DOI: 10.1002/pssa.202000447
|View full text |Cite
|
Sign up to set email alerts
|

Direct Heteroepitaxy and Selective Area Growth of GaP and GaAs on Si by Hydride Vapor Phase Epitaxy

Abstract: Direct heteroepitaxy and selective area growth (SAG) of GaP and GaAs on Si(100) and Si(111) are implemented by low‐pressure hydride vapor phase epitaxy (LP‐HVPE), which are facilitated by buffer layers grown at 410–490 °C with reactive gas mixing directly above Si substrates. High‐density islands observed on GaP buffer layers on Si result in rough morphology and defect formation in the subsequent GaP layers grown at 715 °C. The impact of growth temperature of GaAs buffer layers on the crystal quality of GaAs/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…No significant change in crystalline quality was observed from the addition of Zn-doping during heteroepitaxy of GaP on GaAs. A significant improvement in crystalline quality of GaP grown on Si by HVPE compared to our previous work, reported in [42], was achieved through the pre-heating of the Si substrates in AsH 3 instead of PH 3 . It was also shown that the crystalline quality of GaP/Si could be improved by growing on Si(111) instead of Si(100) and by increasing the GaCl flow.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…No significant change in crystalline quality was observed from the addition of Zn-doping during heteroepitaxy of GaP on GaAs. A significant improvement in crystalline quality of GaP grown on Si by HVPE compared to our previous work, reported in [42], was achieved through the pre-heating of the Si substrates in AsH 3 instead of PH 3 . It was also shown that the crystalline quality of GaP/Si could be improved by growing on Si(111) instead of Si(100) and by increasing the GaCl flow.…”
Section: Discussionmentioning
confidence: 58%
“…However, it is clear that the The pre-heating of the Si substrates in AsH 3 ambient plays an important role in improving the crystalline quality for GaP/Si epitaxy. In our previous work, un-doped GaP layers were grown on Si(100) and Si(111) substrates using similar growth conditions as the ones used for samples E and F, but the substrates were pre-heated in PH 3 ambient instead of AsH 3 [42]. HRXRD omega scans for those samples yielded FWHM of 913 arcseconds and 419 arcseconds for GaP grown on Si(100) and Si(111), respectively.…”
Section: Characterisation Of Heteroepitaxial P-gapmentioning
confidence: 99%